Bee pollen nutritional value and microbiological stability: influence of preservation techniques - Mekki, Imen (2020)
Bee pollen is an important beehive product, with a rich chemical composition and biological properties, which vary according to the region of production, plant age and agroecological conditions. Its moisture content may vary from 18 - 25%, depending on the technique and the time of collection [1]. Bee pollen is subject to proliferation of microbiological contamination that can make its consumption and commercialization unfeasible when not properly preserved, its nutritional value can be rapidly reduced due to Maillard reactions [2].